cis-acting intron mutations that affect the efficiency of avian retroviral RNA splicing: implication for mechanisms of control. - Katz, R A (1988)
The full-length retroviral RNA transcript serves as (i) mRNA for the gag and pol gene products, (ii) genomic RNA that is assembled into progeny virions, and (iii) a pre-mRNA for spliced subgenomic mRNAs. Therefore, a balance of spliced and unspliced RNA is required to generate the appropriate levels of protein and RNA products for virion production. We have introduced an insertion mutation near the avian sarcoma virus env splice acceptor site that results in a significant increase in splicing to form functional env mRNA. The mutant virus is replication defective, but phenotypic revertant viruses that have acquired second-site mutations near the splice acceptor site can be isolated readily. Detailed analysis of one of these viruses revealed that a single nucleotide change at -20 from the splice acceptor site, within the original mutagenic insert, was sufficient to restore viral growth and significantly decrease splicing efficiency compared with the original mutant and wild-type viruses. Thus, minor sequence alterations near the env splice acceptor site can produce major changes in the balance of spliced and unspliced RNAs. Our results suggest a mechanism of control in which splicing is modulated by cis-acting sequences at the env splice acceptor site. Furthermore, this retroviral system provides a powerful genetic method for selection and analysis of mutations that affect splicing control.